2013
DOI: 10.1155/2013/756302
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Hypermethylation of theEMP3Gene in a Series of 229 Human Gliomas

Abstract: The epithelial membrane protein 3 (EMP3) is a candidate tumor suppressor gene in the critical region 19q13.3 for several solid tumors, including tumors of the nervous systems. The aim of this study was to investigate the EMP3 promoter hypermethylation status in a series of 229 astrocytic and oligodendroglial tumors and in 16 GBM cell lines. The analysis was performed by methylation-specific PCR and capillary electrophoresis. Furthermore, the EMP3 expression at protein level was evaluated by immunohistochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 35 publications
1
25
0
1
Order By: Relevance
“…Previous studies reported that CpG island hypermethylation in the EMP3 promoter region is frequent in LGGs [28-30]. Moreover, EMP3 promoter hypermethylation is associated with a favorable prognostic significance in OS in patients with oligodendroglial and glioblastoma [29, 31, 32]. In line with previous studies, we found that promoter methylation in EMP3 correlated negatively with its expression and lower EMP3 expression predicted better prognosis in LGGs patients.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies reported that CpG island hypermethylation in the EMP3 promoter region is frequent in LGGs [28-30]. Moreover, EMP3 promoter hypermethylation is associated with a favorable prognostic significance in OS in patients with oligodendroglial and glioblastoma [29, 31, 32]. In line with previous studies, we found that promoter methylation in EMP3 correlated negatively with its expression and lower EMP3 expression predicted better prognosis in LGGs patients.…”
Section: Discussionsupporting
confidence: 90%
“…EGFR gene amplification, as well as LOH on the 9p chromosome arm, was not found in our three cases. The presence of EMP3 promoter hypermethylation in Case 2 is remarkable, as this epigenetic alteration is typical of oligodendrogliomas, where it is mainly associated with the 1p/19q co-deletion 23. As such, its occurrence in Case 2 could be in line with the diagnosis of oligodendroglioma at the first intervention.…”
Section: Discussionmentioning
confidence: 59%
“…It is common in pure (63%) and mixed (70%) oligodendroglial tumors in comparison to astrocytic ones (18%). It prevails in grade II (71.4%) upon grade III (44.7%) gliomas, and in secondary (89%) upon primary GBMs (17%) (Alaminos et al, 2005;Li et al, 2007;Kunitz et al, 2007;Mellai et al, 2013). Not found in GBM cell lines (Ernst et al, 2009).…”
Section: Brain Tumors / Gliomasmentioning
confidence: 99%
“…It is strongly associated with IDH1/IDH2 somatic mutations in astrocytic and oligodendroglial tumors and inversely correlated with EGFR gene amplification. In oligodendrogliomas, it is also associated with loss of the 19q13.3 locus and with total 1p/19q co-deletion (Tews et al, 2006;Mellai et al, 2013), with prognostic significance on patient overall survival (Kunitz et al, 2007;Mellai et al, 2013). The EMP3 gene belongs to the glioma CpG island methylator phenotype (G-CIMP) (Noushmehr et al, 2010), that identifies a distinct molecular glioma subclass, prevalent in low-grade tumors and associated with IDH1/2 mutations and with improved patient survival (Laffaire et al, 2011).…”
Section: Brain Tumors / Gliomasmentioning
confidence: 99%